Upaya Pemenuhan Hak Pelayanan Kesehatan Kepada Narapidana Di Lembaga Pemasyarakatan - Faldi Biaggy Fachrezi; Padmono Wibowo (Widya Yuridika, 2020)
This study aims to determine the process of fulfilling prisoners' rights in obtaining proper health and food services in the review of the law, as well as the obstacles faced by prisons in providing appropriate health and food services in Correctional Institutions. This research is normative legal research. This research focuses more on secondary data. The primary secondary legal material is from laws relating to prisoners' health rights. Data analysis method used is qualitative analysis. Based on the research conducted, it can be concluded that the fulfillment of prisoners' rights to get proper health and food services in the review of the act in Correctional Institution has not been going well because of the various kinds of obstacles faced by the correctional institutions, such constraints include over capacity in prison, there is still a lack of special expertise in the field of health in prison and prison is still constrained by limited funding.